The Effect of Regional Financial Networks on Banking System Stability in Indonesia: A Literature Review of Linkages, Risks, and Impacts in a Macroeconomic Context - Loso Judijanto; Eva Yuniarti Utami; Eko Sudarmanto; Nova Erliyana; Saida Said (Sciences du Nord Economics and Business, 2024)
This research conducts a comprehensive literature analysis to explore the linkages, risks, and impacts of regional financial networks on banking system stability in Indonesia within the broader macroeconomic context. The systematic review synthesizes findings from diverse studies, examining both positive and negative dynamics associated with regional financial integration. Positive linkages include enhanced risk-sharing mechanisms and improved access to financial resources, while negative linkages encompass susceptibility to contagion effects and systemic risks. The associated risks, such as credit, market, and operational risks, are identified and discussed. Additionally, the research delves into the multifaceted impacts of regional financial networks on economic growth, financial inclusion, and the resilience of Indonesia's banking sector to external shocks. The synthesis of these findings provides valuable insights for policymakers, financial institutions, and researchers to navigate the challenges and leverage opportunities presented by regional financial networks.